Evolutionary regulatory dynamics in a pluralist and polarized journalism landscape: a case study of the normative framework in Spanish media - Seijas Costa, Raquel; Barredo Ibáñez, Daniel; Cea Esteruelas, Nereida (Frontiers in Communication, 2024)
Within the European Union, the pluralist polarized journalistic model suggests the presence of journalistic cultures rooted in the connections between political parties and media organizations. In this classical framework, the state exerts significant intervention to influence a media system characterized by lower levels of professionalization. In this regard, Spain serves as a well-examined example of a pluralist polarized Western democracy. Our study entails a systematic review based on two distinct dimensions. Firstly, we scrutinized all legal documents pertaining to media regulation in Spain published between the Spanish transition and the present 1977-2024. From this perspective, we propose a chronological evolution to categorize this extensive collection of norms. Secondly, we complement our primary source assessment with an examination of secondary sources to validate the proposed evolution. Our findings indicate that the Spanish media regulation is evolving due to two pivotal factors: the influence of the European Union and the preservation of the narrative established during the transition to democracy. While contemporary communication grapples with issues such as the rise of artificial intelligence, journalistic instability, algorithmic communication, and fragmented user consumption, these areas are only addressed peripherally within the Spanish media normative context.